A common FADS2 promoter polymorphism increases promoter activity and facilitates binding of transcription factor ELK1 - E. Lattka; S. Eggers; G. Moeller; K. Heim; M. Weber; D. Mehta; H. Prokisch; T. Illig; J. Adamski (Journal of Lipid Research, 2010)
Fatty acid desaturases (FADS) play an important role in the formation of omega-6 and omega-3 highly unsaturated fatty acids (HUFAs). The composition of HUFAs in the human metabolome is important for membrane fluidity and for the modulation of essential physiological functions such as inflammation processes and brain development. Several recent studies reported significant associations of single nucleotide polymorphisms (SNPs) in the human FADS gene cluster with HUFA levels and composition. The presence of the minor allele correlated with a decrease of desaturase reaction products and an accumulation of substrates. We performed functional studies with two of the associated polymorphisms (rs3834458 and rs968567) and showed an influence of polymorphism rs968567 on FADS2 promoter activity by luciferase reporter gene assays. Electrophoretic mobility shift assays proved allele-dependent DNA-binding ability of at least two protein complexes to the region containing SNP rs968567. One of the proteins binding to this region in an allele-specific manner was shown to be the transcription factor ELK1 (a member of ETS domain transcription factor family). These results indicate that rs968567 influences FADS2 transcription and offer first insights into the modulation of complex regulation mechanisms of FADS2 gene transcription by SNPs.